Hubungan Pengetahuan Kepala Keluarga Tentang Covid-19 dengan Menerapkan Kepatuhan Prokes di Jetis Wetan Gunungkidul - Ratna Lestari; Devi Alfian (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: The number of COVID-19 cases highly increased nowadays. The massive spread can’t be avoidable. To stop spreading of the outbreak, we need the better knowledge and the compliance of health protocols as a habit. The head of the family has role as an educator and role model in preventing COVID-19 for their family members. Purpose: This study aims to know the knowledge of the head of the family about COVID-19 and their compliance of health protocols in Dusun Jetis Wetan Pacarejo Semanu Gunungkidul. Method: This research is a quantitative study with a correlational design using a Cross-Sectional approach. 74 heads of family were involved in this study. The sampling technique used proportional sampling and the simple random sampling used as the data collection technique. This research was conducted in Dusun Jetis Wetan Pacarejo Semanu Gunungkidul, the data collection was carried out for 8 days from April 7 to April 14, 2022. This study used a questionnaire about COVID-19 knowledge and the compliance of health protocols. Bivariate data analysis used Somers'd test. Result: The results show that majority knowledge of head family insufficient category with 38 people or 51.4% of the respondents, the level of compliance of the majority respondents was ‘not compliant’ as many as 38 people or 51.4%. p = 0.000 (p < 0.05), which means that there is a significant correlation with a correlation coefficient of 0.841. Conclusion: There is a correlation between family knowledge of COVID-19 and compliance to apply health protocols.